2005
DOI: 10.1074/jbc.m504347200
|View full text |Cite
|
Sign up to set email alerts
|

Cl– Interference with the Epithelial Na+ Channel ENaC

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR) is a protein kinase A and ATP-regulated Cl ؊ channel that also controls the activity of other membrane transport proteins, such as the epithelial Na Inhibition by Cl ؊ was reduced in trimeric channels with a truncated COOH terminus of ␤ENaC and ␥ENaC, and it was no longer detected in dimeric ␣⌬C␤ ENaC channels. Deletion of the NH 2 terminus of ␣-, ␤-, or ␥ENaC, mutations in the NH 2 -terminal phosphatidylinositol bisphosphate-binding domain of ␤ENa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 63 publications
0
44
0
Order By: Relevance
“…For example, CFTR physically situated near ENaC could impact signaling pathways that control the trafficking and surface expression of ENaC (13). Other processes or conditions important for ENaC activity could be influenced by the effects of CFTR on the pH near the apical surface (44,45) or intracellular ion content (46,47). Importantly, our results provide a concrete mechanism of CFTR negative regulation of ENaC in airway epithelia while leaving open the possibility that other modes of ENaC regulation are utilized in epithelia with different salt and water physiology.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CFTR physically situated near ENaC could impact signaling pathways that control the trafficking and surface expression of ENaC (13). Other processes or conditions important for ENaC activity could be influenced by the effects of CFTR on the pH near the apical surface (44,45) or intracellular ion content (46,47). Importantly, our results provide a concrete mechanism of CFTR negative regulation of ENaC in airway epithelia while leaving open the possibility that other modes of ENaC regulation are utilized in epithelia with different salt and water physiology.…”
Section: Discussionmentioning
confidence: 99%
“…This is well illustrated by the clearance of the lung fluid at birth, which is due to the activation of the epithelial Na ϩ channels in the respiratory epithelium (4). Similarly, the dehydration of the respiratory surface which is observed in cystic fibrosis appears to be due to the increased activity of the epithelial Na ϩ channels consequent on the loss of the normal inhibitory effects of CFTR (2,29). On the other hand, inactivating mutations of the epithelial Na ϩ channels, as occur in pseudohypoaldosteronism type I, lead to fluid accumulation in the respiratory tract (19).…”
mentioning
confidence: 88%
“…Some have suggested that the decrease in ENaC-mediated currents reflects a series resistor error (23,24). Others have suggested that this decrease in ENaC functional expression requires CFTR-mediated Cl Ϫ transport (2,20). Such transport would presumably lead to an increase in cytosolic Cl Ϫ concentration, which can inhibit ENaC-mediated Na ϩ transport (10).…”
Section: Functional Expression Of N1303k-cftr In Xenopus Oocytesmentioning
confidence: 99%